Anemia management in dialysis patients: a PIVOT and a new path?. Issue 3 (May 2020) - Nair, Sanjeev; Trivedi, Mayuri
Abstract : Purpose of review: We will examine the current and future options in management of anemia in dialysis patients focusing on recent trials in iron supplementation and alternatives to erythropoietin-stimulating agents (ESAs). Recent findings: We review the literature on Erythropoietin (EPO)-stimulating agents, focusing on the risk benefits of various options available. We review the recent practice changing trial in iron supplementation in dialysis patients with chronic kidney disease and movements in the research on alternatives to EPO-stimulating agents primarily hypoxia-inducible factor prolyl hydroxylase inhibitors (HIF-PHIs). Summary: ESAs constitute the mainstay of treatment of anemia in dialysis and evidence does not support the preference of any one type over the other. But concerns exist about the cardiovascular safety of supra-physiological ESA levels. Iron supplementation has been shown to be a well tolerated method to decrease ESA doses while maintaining hemoglobin levels and recent evidence should result in a revisiting of the guidelines for iron supplementation. HIF-PHIs are potentially safe alternatives to ESAs that correct and maintain hemoglobin while maintaining physiological levels of erythropoietin. Ongoing phase III trials for these drugs will likely answer questions of long-term safety regarding these drugs.